KAJIAN DERET FIBONACCI DAN GOLDEN RATIO DALAM PENCIPTAAN LAGU - Harry Mahardika, Putu; Putu Ida Harini, Luh; Eka Nila Kencana, I Putu (Universitas Ahmad Dahlan, 2012)
In mathematics, beauty can be thought of as a